2015
DOI: 10.1016/j.jes.2014.05.056
|View full text |Cite
|
Sign up to set email alerts
|

Serious BTEX pollution in rural area of the North China Plain during winter season

Abstract: Atmospheric BTEX compounds (benzene, toluene, ethylbenzene and xylenes) in a rural site of the North China Plain (NCP) were preliminarily investigated in winter, and the outdoor concentrations (25.8-236.0 μg/m 3 ) were found to be much higher than those reported in urban regions. The pollution of BTEX inside a farmer's house was even more serious, with combined concentrations of 254.5-1552.9 μg/m 3 . Based on the ratio of benzene to toluene (1.17 ± 0.34) measured, the serious BTEX pollution in the rural site w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Similarly to benzene, indoor toluene maximum level of 29.5 ppb measured in this study, is higher than those reported in most of the previous studies of air quality in schools (see Table 1). However, toluene concentration was lower than the values ranging between 0 and 106.3 ppb found in other indoor environments such as universities (Can et al 2015;Yurdakul et al 2017), or urban and rural dwellings (Liu et al 2015;Bari et al 2015). Most of studies indicate that main sources of toluene are indoor ones (Ilgen et al 2001;Kotzias et al 2009).…”
Section: Toluenementioning
confidence: 89%
“…Similarly to benzene, indoor toluene maximum level of 29.5 ppb measured in this study, is higher than those reported in most of the previous studies of air quality in schools (see Table 1). However, toluene concentration was lower than the values ranging between 0 and 106.3 ppb found in other indoor environments such as universities (Can et al 2015;Yurdakul et al 2017), or urban and rural dwellings (Liu et al 2015;Bari et al 2015). Most of studies indicate that main sources of toluene are indoor ones (Ilgen et al 2001;Kotzias et al 2009).…”
Section: Toluenementioning
confidence: 89%
“…The content of toluene in gasoline and exhaust gases is 3-4-fold higher than the benzene content (Brocco et al, 1997). T/B ratios b1 indicate that the primary source of BTEX is biomass, biofuel, or coal burning, while T/B N 1 indicates that it mainly originates from vehicle emissions (Liu et al, 2015). The varying T/B observed during 2015-2019 indicated the complex nature of BTEX in the ambient air of Almaty (Fig.…”
Section: Identification Of Btex Emission Sourcesmentioning
confidence: 96%
“…At sub 0 °C sampling temperatures, T/B ratios were below 1.0 in 15 out of 18 samples. Such ratios may indicate that significant fractions of BTEX at the time of sampling originated from non-traffic related sources [27,28]. At lower temperatures, main sources of BTEX are most likely originating from power plants and residential heating, most of which still use coal as a fuel.…”
Section: Identification Of Btex Emission Sourcesmentioning
confidence: 99%